The speed and legibility of handwriting in dyslexic students - Cardoso, Monique Herrera [UNESP]; dos Santos, Natália Lemes [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2018)
This chapter aims to compare the speed and legibility of handwriting of dyslexic students with the ones with good academic performance. Sixty-four students participated in the study; 07 dyslexic students of both genders, aged from 9 to 13 years and 1 month, composed group I (GI); and 57 students with good academic performance, of both genders, aged from 9 to 13 years and 1 month composed group II (GII). For the accomplishment of the study, the translated and adapted version of DASH was applied to Brazilian Portuguese, which consists of five tasks: Copy Best, Alphabet Writing, Copy fast of a sentence, Graphic speed and Free thematic writing. For the calculation of the writing speed, legible and illegible words per minute (LWPM/IWPM) were considered in the tasks Copy best, Copy fast of a sentence and Free thematic writing, the legible or illegible letters per minute (LLPM/ILPM) in the Alphabet Writing task, and the amount of X marked correctly in one minute in the Graphic speed task. It was possible to observe that GI presented inferior performance in LWPM and LLPM and superior performance in IWPM and ILPM, when compared to GII. In addition, GI still performed poorly on the Graphic speed task, when compared to GII students. Thus, it can be concluded that the performance in speed and legibility of writing of Brazilian dyslexics is inferior to students with good academic performance, and delay is observed in the percepto-viso-motor skills of dyslexics. Further studies are needed to investigate the correlation of calligraphy and motor skills, visual perceptive, attentional, memory and access to language codes, in order to better understand how these underlying factors may interfere and reflect on students' handwriting with dyslexia, in order to assist in the differential diagnosis and provide directions for health and education professionals, regarding interventions with calligraphic problems.
Keywords: Assessment; Dyslexia; Handwriting